Beveridge Report (Pictorial charts with explanatory notes) - Beveridge, William Henry Beveridge, Baron, 1879-1963. Social insurance and allied services
1943-01 1943 1940s 14 pages : illustrations TABLES. Chart 1. C0NTRIBUTIONS TO BENEFITS. (For figures of contributions see chart 3.) BENEFITS. Shillings per week. Unemployment, Disability and Training Benefit. Man and not gainfully occupied wife (joint benefit) 40/- Man with gainfully occupied wife not on benefit 24/- Single man or woman, aged 21 and upwards 24/- Single man or woman aged 18-20 20/- Boys or girls 16-17 15/- Married woman gainfully occupied when herself on benefit 16/- Retirement Pension for men aged 65 and women aged 60 (after transition period). Man and not gainfully occupied wife (joint pension) 40/- basic Single man or woman, man with gainfully occupied wife, woman contributor with husband below pensionable age (single person) 24/- basic Addition to basic pension for postponement, in respect of each year of postponement On joint pension 2/- On single pension 1/- Maternity Benefit (13 weeks) Married woman gainfully occupied whether paying contributions or exempt, in addition to maternity grant 36/- Widow's Benefit (13 weeks) 36/- Guardian Benefit* 24/- Dependant Allowance Dependant above age for children's allowance of person receiving unemployment, disability or training benefit 16/- Children's Allowance. For each child when responsible parent is in receipt of any benefit or pension, and for each child after the first in other cases, allowances graded by age averaging over all children in addition to existing provision in kind 8/- * Retirement Pension and Guardian Benefit are subject to partial reduction for earnings. The transition period suggested is 20 years. At the beginning of the period pensions are 25/- for man and wife and 14/- for single person. 126/TG/377/1/1/153